Best Practice Guidelines for Surgical Site Infection in High-risk Pediatric Spine Surgery: Definition, Prevention, Diagnosis, and Treatment. Issue 10 (29th November 2022) - Badin, Daniel; Leland, Christopher R.; Matsumoto, Hiroko; Roye, Benjamin; Vitale, Michael; Flynn, John; Samdani, Amer; Larson, A. Noelle; Yaszay, Burt; Pahys, Joshua; Glotzbecker, Michael; Bachmann, Keith R.; et al.
Abstract : Background: Prior "best practice guidelines" (BPG) have identified strategies to reduce the risk of acute deep surgical site infection (SSI), but there still exists large variability in practice. Further, there is still no consensus on which patients are "high risk" for SSI and how SSI should be diagnosed or treated in pediatric spine surgery. We sought to develop an updated, consensus-based BPG informed by available literature and expert opinion on defining high-SSI risk in pediatric spine surgery and on prevention, diagnosis, and treatment of SSI in this high-risk population. Materials and Methods: After a systematic review of the literature, an expert panel of 21 pediatric spine surgeons was selected from the Harms Study Group based on extensive experience in the field of pediatric spine surgery. Using the Delphi process and iterative survey rounds, the expert panel was surveyed for current practices, presented with the systematic review, given the opportunity to voice opinions through a live discussion session and asked to vote regarding preferences privately. Two survey rounds were conducted electronically, after which a live conference was held to present and discuss results. A final electronic survey was then conducted for final voting. Agreement ≥70% was considered consensus. Items near consensus were revised if feasible to achieve consensus in subsequent surveys. Results: Consensus was reached for 17 items for defining high-SSI risk, 17 items for preventing, 6 for diagnosing, and 9 for treating SSI in this high-risk population. After final voting, all 21 experts agreed to the publication and implementation of these items in their practice. Conclusions: We present a set of updated consensus-based BPGs for defining high-risk and preventing, diagnosing, and treating SSI in high-risk pediatric spine surgery. We believe that this BPG can limit variability in practice and decrease the incidence of SSI in pediatric spine surgery. Level of Evidence: Not applicable.